2007
DOI: 10.1038/sj.npp.1301588
|View full text |Cite
|
Sign up to set email alerts
|

Rats with Extended Access to Cocaine Exhibit Increased Stress Reactivity and Sensitivity to the Anxiolytic-Like Effects of the mGluR 2/3 Agonist LY379268 during Abstinence

Abstract: Metabotropic glutamate 2/3 receptors (mGluR2/3) are emerging targets for the reduction of stress that contributes to drug relapse. The effect of a history of cocaine escalation on stress reactivity during abstinence and the role of mGlu2/3 receptors in stress in these animals were tested. Experiment 1FRats trained to self-administer cocaine, under short (ShA, 1-h) or long (LgA, 6-h) access conditions, or noncaloric food pellets (Ctrl, 1-h), were tested for stress reactivity in the shock-probe defensive burying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 52 publications
6
42
1
Order By: Relevance
“…Escalation of cocaine-seeking in rats has also been proposed to model some aspects of addiction (Ahmed and Koob, 1998;Lenoir et al, 2012), and a previous report reported that LY379268 blunted motivation for cocaine more efficaciously (ie, at lower dose) in long-access cocaine-escalated rats than in short-access rats (Hao et al, 2010). Furthermore, rats trained with a longaccess cocaine method showed a stable, elevated anxietylike behavior up to 42 days after discontinuation of cocainetaking that was higher than in short-access animals; importantly, long-access rats were more sensitive to the anxiolytic effect of LY379268 than short-access rats (Aujla et al, 2008). These results are consistent with our report that 3.0 mg/kg of LY379268 seems to have a longer lasting effect in addict-like than in non-addict-like rats in a cuereinstatement session (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Escalation of cocaine-seeking in rats has also been proposed to model some aspects of addiction (Ahmed and Koob, 1998;Lenoir et al, 2012), and a previous report reported that LY379268 blunted motivation for cocaine more efficaciously (ie, at lower dose) in long-access cocaine-escalated rats than in short-access rats (Hao et al, 2010). Furthermore, rats trained with a longaccess cocaine method showed a stable, elevated anxietylike behavior up to 42 days after discontinuation of cocainetaking that was higher than in short-access animals; importantly, long-access rats were more sensitive to the anxiolytic effect of LY379268 than short-access rats (Aujla et al, 2008). These results are consistent with our report that 3.0 mg/kg of LY379268 seems to have a longer lasting effect in addict-like than in non-addict-like rats in a cuereinstatement session (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Because mGlu2/3 receptors negatively regulate glutamatergic transmission, we postulate that mGlu2/3 receptor function is rapidly upregulated in the presence of a nicotine-associated context to counteract the context-induced enhancement of glutamatergic transmission. Recent studies reported that upregulation in mGlu2/3 receptor function may be responsible for the increased pharmacological efficacy of the mGlu2/3 agonist LY379268, resulting in a leftward shift of the dose-response curve (Aujla et al, 2008;Hao et al, 2010). Thus, based on the results from these studies and our findings, we hypothesize that the nicotine-associated context resulted in rapid upregulation of mGlu2/3 receptors, which in turn enhanced the pharmacological efficacy of LY379268, resulting in the attenuation of nicotine-induced increases in NAcc shell dopamine only in the presence of a nicotine-associated context.…”
Section: Discussionmentioning
confidence: 99%
“…For example, intermittent, but extended, access to substances of abuse, such as ethanol (8,19,24,29,66), nicotine (35,66), cocaine (1,2,5,49,62,69,95), heroin (3,56), and methamphetamine (48) induces behavioral and molecular adaptations in rodents which resemble features of drug dependence in humans (54,99), including increased drug self-administration. Drug addicts themselves often show cyclic patterns of uncontrolled use vs. abstinence, a profile also modeled by intermittent access animal models.…”
mentioning
confidence: 99%